2014
DOI: 10.1051/matecconf/20141501010
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Survey on Causes of Delay in Malaysian Construction Project

Abstract: Abstract. Construction delay is a common problem in the construction industry all over the world. Many researchers seeking the causes of delay in order to reduce the probability of delay to occur. Most researcher identified causes of delay in construction to reduce the possibility of construction project to continued delay. This study is to obtain the holistic delay categories base on Drewin Open Conversion System (DOCS) for the development of a theoretical framework delay and to get the most significant cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The central idea of this study is led by the numbers of issues involved in the project construction industry determined by several papers (Zidane & Andersen, 2018;Shah, 2016;Tawil et al, 2014;Santoso & Soeng, 2016;Durdyev & Hosseini, 2019;Oshungade & Kruger, 2017;Aziz & Abdel-Hakam, 2016;Nyoni & Bonga, 2017;Nawi et al, 2016;Banobi & Jung, 2019;Gamil & Rahman, 2017;Olanrewaju et al, 2017;Gómez-ferrer, 2017;Alzeraa et al, 2018). Those studies identified many issues and one of the issues is communication.…”
Section: Research Gap -Current Research On Communication Problems In ...mentioning
confidence: 99%
“…The central idea of this study is led by the numbers of issues involved in the project construction industry determined by several papers (Zidane & Andersen, 2018;Shah, 2016;Tawil et al, 2014;Santoso & Soeng, 2016;Durdyev & Hosseini, 2019;Oshungade & Kruger, 2017;Aziz & Abdel-Hakam, 2016;Nyoni & Bonga, 2017;Nawi et al, 2016;Banobi & Jung, 2019;Gamil & Rahman, 2017;Olanrewaju et al, 2017;Gómez-ferrer, 2017;Alzeraa et al, 2018). Those studies identified many issues and one of the issues is communication.…”
Section: Research Gap -Current Research On Communication Problems In ...mentioning
confidence: 99%
“…Muhwezi et al [74]; Rahimipour and Shahhosseini [77]; Tawil et al [79]; Amoatey et al [81]; Shehu et al [83]; Gajare and Attarde [85]; Bekr [87]; Khan [76]; Al-Emad and Nagapan [88]; Dontul et al [94]; Suksai et al [89]; Van [110]; Zidane and Andersen [112] It is still a fact that the employer-caused delay aspects have been either not addressed or partially addressed. For instance, Wang et al [116] have reviewed the construction delay in the Chinese building projects in which 14 employer-caused delay factors have not been considered, such as employer interference, employer variations/changes in scope, and defective materials provided by the employer.…”
Section: -16mentioning
confidence: 99%
“…For instance, environmental aspects are partially considered in most cases. For example, Muhwezi et al [74] included the factor "Natural disasters (flood, hurricane, earthquake)" only, whereas Tawil et al [79] only considered "Bad weather conditions" and "Natural disasters" under environmental aspects. Concerning contractual aspects, Muhwezi et al [74] [76] included the factors of "Inadequate planning and scheduling," "Inadequate contractor experience," "Lack of coordination at the site," "Contractor's lack of planning at preconstruction," "Poor site management and supervision," "Unsuitable management structure of the contractor," "Lack of communication," "Inappropriate overall organization structure," "Poor managerial skills," "Inadequate control over site resource allocation," "Unsuitable leadership of contractor's management," and "Improper incentive policy."…”
Section: Research Gaps In Terms Of Delay Aspectsmentioning
confidence: 99%